Evaluating the Success of a Parent-Professional Autism Network: Implications for Family Counselors. (July 2013) - Lock, Robin H.; Bradley, Loretta; Hendricks, Bret; Brown, Donna B.
Family counselors working with families and children diagnosed with autism spectrum disorders may seek assistance from a variety of sources in order to support their clients. Despite the need, few community resources are available to meet the varied and complex needs of families. The authors discuss a community-based program that can be used as an adjunct to family counseling. Specifically, this study used a survey and interview to examine perceptions of the benefits of participation in this program. The study identified four themes: (1) knowledge, (2) altered living patterns, (3) heightened coping skills, and (4) desired changes. These themes supported parental views of the success of the parent-professional networking group. Considerations for both family counseling practice and research are considered.